2021
DOI: 10.1093/jscr/rjab312
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor nerve palsy following coronary artery bypass graft surgery: can pituitary apoplexy complicate the post-operative course of cardiac surgery?

Abstract: Oculomotor nerve palsy, due to pituitary apoplexy, has been previously reported in the literature. However, the association with coronary artery bypass graft surgery (CABG) is rarely investigated. This article reports a case of pituitary apoplexy presenting with oculomotor nerve palsy following CABG. A 65-year-old male, known to have ischemic heart disease, diabetes mellitus and hypertension, presented with ptosis, diplopia and anisocoria that developed after 1 day of CABG. Radiological imaging demonstrated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…( Table 1 ) Headache was severe, often described as the most painful headache episode an individual has ever experienced, and graded, for example, as high as 9 on a scale from 0 to 10, with 10 being the most severe in one study [ 31 ]. For practical purposes we point out that headache was absent in some cases; thus, an index of suspicion should be provided by other endocrine and non-endocrine clinical elements [ 43 , 86 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ]. For instance, Enatsu et al reported a 65-year-old woman admitted for a nonfunctioning pituitary adenoma-associated PA who presented third cranial nerve palsy and sudden decrease in visual acuity unaccompanied by headache [ 196 ].…”
Section: Pitnet Complicated With Pamentioning
confidence: 99%
See 3 more Smart Citations
“…( Table 1 ) Headache was severe, often described as the most painful headache episode an individual has ever experienced, and graded, for example, as high as 9 on a scale from 0 to 10, with 10 being the most severe in one study [ 31 ]. For practical purposes we point out that headache was absent in some cases; thus, an index of suspicion should be provided by other endocrine and non-endocrine clinical elements [ 43 , 86 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ]. For instance, Enatsu et al reported a 65-year-old woman admitted for a nonfunctioning pituitary adenoma-associated PA who presented third cranial nerve palsy and sudden decrease in visual acuity unaccompanied by headache [ 196 ].…”
Section: Pitnet Complicated With Pamentioning
confidence: 99%
“…For instance, Enatsu et al reported a 65-year-old woman admitted for a nonfunctioning pituitary adenoma-associated PA who presented third cranial nerve palsy and sudden decrease in visual acuity unaccompanied by headache [ 196 ]. Another example is a 65-year-old male who developed PA as a post-operative complication after a coronary artery surgery; he only presented diplopia and third cranial nerve palsy [ 214 ]. Other circumstances without headaches involve a comatose status.…”
Section: Pitnet Complicated With Pamentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 It has been hypothesized that pituitary apoplexy during on-pump cardiac surgery is likely related to cerebral hypoperfusion, low perfusion pressures, hemodilution and non-pulsatile flow experienced while on cardiopulmonary bypass. 3 Pituitary adenoma tissue is markedly more susceptible to ischemia and hemorrhage at baseline, likely due to both the thin-walled and abnormal sinusoidal nature of the tumor's vasculature; thrombotic events of atherosclerotic plaques and microvascular embolization while on-pump have also been implicated. 4 While the literature does include approximately 20 reports of pituitary apoplexy-induced ophthalmoplegia after both on and off-pump coronary revascularization, never before has pituitary adenoma recurrence after prior resection and subsequent apoplexy leading to severe ophthalmoplegia after on-pump CABG been described.…”
Section: Commentmentioning
confidence: 99%